La revocatoria del mandato presidencial (2016)
The exercise of political power and legitimacy of it has often been the subject of great conflict, which despite being regrettable, have impacted positively for the creation and development of existing constitutional institutions; so, institutions such as popular sovereignty, participatory democracy, participatory democracy, political control or governance systems as the rule of law. So, Colombia has been influenced by the great social currents, as evidenced by the 1991 constitution introduced by national principles such as popular sovereignty and thus the possibility of political control of the ruled over the rulers, by programmatic vote that close relationship each other. Moreover, within the existing legal system, the people or acquires an active role in the development and control of political power, that through the implementation of mechanisms for citizen participation; within this, highlights the revocation of the mandate contained in the words of the Constitutional Court is the ideal medium for materializing the political control of the primary constituent of their representatives; however, this institution can only be exercised against the mandate of governors and mayors not the president